(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In Tumor Diseases, the spectrum of kidney damage is very wide and can be caused directly by tumor infiltration and the effects of tumor cell metabolites on kidney tissue, glomerular lesions, as well as nephrotoxic effects of chemotherapy drugs. In addition to the successes achieved in the treatment of Tumor Diseases, the toxicity of the treatment is a huge problem.